Foundation Settlement Prediction Based on a Novel NGM Model. (23rd March 2014) - Chen, Peng-Yu; Yu, Hong-Ming
Abstract : Prediction of foundation or subgrade settlement is very important during engineering construction. According to the fact that there are lots of settlement-time sequences with a nonhomogeneous index trend, a novel grey forecasting model called NGM ( 1, 1, k, c ) model is proposed in this paper. With an optimized whitenization differential equation, the proposed NGM ( 1, 1, k, c ) model has the property of white exponential law coincidence and can predict a pure nonhomogeneous index sequence precisely. We used two case studies to verify the predictive effect of NGM ( 1, 1, k, c ) model for settlement prediction. The results show that this model can achieve excellent prediction accuracy; thus, the model is quite suitable for simulation and prediction of approximate nonhomogeneous index sequence and has excellent application value in settlement prediction.